The prevalence of Borrelia miyamotoi infection, and co-infections with other Borrelia spp. in Ixodes scapularis ticks collected in Canada - Dibernardo, Antonia (BioMed Central, 2014)
BACKGROUND: Blacklegged ticks, Ixodes scapularis are vectors of the tick-borne pathogens Borrelia burgdorferi, Anaplasma phagocytophilum and Babesia microti. Recently, the I. scapularis-borne bacterium Borrelia miyamotoi has been linked to human illness in North America. The range of this tick is expanding in Canada which may increase the potential for human exposure to these agents. METHODS: In this study, 4938 I. scapularis ticks collected in 2012 were tested following a newly developed PCR-based testing protocol to determine the prevalence of infection with B. miyamotoi and other pathogens in I. scapularis in Canada. RESULTS: Borrelia miyamotoi was detected in blacklegged ticks from all provinces except Newfoundland, although the infection prevalence was low (<1%). There was significant variation among provinces in the prevalence of infection of ticks with B. burgdorferi and A. phagocytophilum, but not with B. miyamotoi. CONCLUSIONS: Given the widespread distribution of B. miyamotoi, infection due to this agent should be considered in patients who have been exposed to blacklegged ticks in Canada.